The Role of EGFR/PI3K/Akt/cyclinD1 Signaling Pathway in Acquired Middle Ear Cholesteatoma - Wei Liu; Hongmiao Ren; Jihao Ren; Tuanfang Yin; Bing Hu; Shumin Xie; Yinghuan Dai; Weijing Wu; Zian Xiao; Xinming Yang; Dinghua Xie (Mediators of Inflammation)
Cholesteatoma is a benign keratinizing and hyper proliferative squamous epithelial lesion of the temporal bone. Epidermal growth factor (EGF) is one of the most important cytokines which has been shown to play a critical role in cholesteatoma. In this investigation, we studied the effects of EGF on the proliferation of keratinocytes and EGF-mediated signaling pathways underlying the pathogenesis of cholesteatoma. We examined the expressions of phosphorylated EGF receptor (p-EGFR), phosphorylated Akt (p-Akt), cyclinD1, and proliferating cell nuclear antigen (PCNA) in 40 cholesteatoma samples and 20 samples of normal external auditory canal (EAC) epithelium by immunohistochemical method. Furthermore, in vitro studies were performed to investigate EGF-induced downstream signaling pathways in primary external auditory canal keratinocytes (EACKs). The expressions of p-EGFR, p-Akt, cyclinD1, and PCNA in cholesteatoma epithelium were significantly increased when compared with those of control subjects. We also demonstrated that EGF led to the activation of the EGFR/PI3K/Akt/cyclinD1 signaling pathway, which played a critical role in EGF-induced cell proliferation and cell cycle progression of EACKs. Both EGFR inhibitor AG1478 and PI3K inhibitor wortmannin inhibited the EGF-induced EGFR/PI3K/Akt/cyclinD1 signaling pathway concomitantly with inhibition of cell proliferation and cell cycle progression of EACKs. Taken together, our data suggest that the EGFR/PI3K/Akt/cyclinD1 signaling pathway is active in cholesteatoma and may play a crucial role in cholesteatoma epithelial hyper-proliferation. This study will facilitate the development of potential therapeutic targets for intratympanic drug therapy for cholesteatoma.